Effect of Sales Growth, Profitability, Liquidity, and Leverage on Profit Growth - Yasir Maulana; Elda Mesyani (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this research is to analyze the relationship between sales growth, profitability, liquidity, and leverage at publicly traded food and beverage firms in Indonesia from 2011 to 2019. From 2011-2019, 26 food and beverage companies were listed on the IDX; 11 of these were randomly selected to be included in the study. Here, Eviews is employed to run a random effect panel data regression model. Profit growth of food and beverage firms listed on the IDX between 2011 and 2019 was found to be significantly influenced by sales growth, profitability (ROE), liquidity (Cash Ratio), and leverage (DAR). For the period 2011-2019, food and beverage firms included on the IDX have had a positive and statistically significant impact from Sales Growth on their Profit Growth. Companies in the food and beverage sector that are part of the IDX and have a positive return on equity (ROE) will see their profits increase over the 2011-2019 time period. During the period 2011-2019, the profit growth of food and beverage companies listed on the IDX was negatively and significantly impacted by both liquidity (Cash Ratio) and leverage (DAR).